2002
DOI: 10.1046/j.1468-1331.2002.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual cortex excitability in migraine before and after valproate prophylaxis: a pilot study using TMS

Abstract: We examined the effect of standard migraine prophylaxis with sodium valproate on repeated measures of occipital excitability using transcranial magnetic stimulation (TMS). We predicted that, comparing pre- and post-treatment assessments, a reduction in clinical migraine parameters would be paralleled by a decrease in excitability measurements.A total of 31 migraine patients enrolled in the study, for assessment prior to and 1 month after commencement of sodium valproate prophylaxis. At each assessment, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…In their recent review the authors [8] indeed consider that the reduced HFO, evidenced in somatosensory potential (reflecting a reduced thalamo-cortical activation), could underlie the basal hypo-activity of the sensory cortices. In our opinion the reduced efficiency of inhibitory circuits could represent a valid background to impaired habituation, in migraine as a consistent bulk of evidence supports the reduced activity of inhibitory circuits in migraine [13, 14, 29, 30, 38, 39, 42, 43, 46, 4850]. This could apply not only for cortical but also for sub-cortical structures (see lack of habituation of BR) where it could occur through local GABA dysfunction (see Harsing 2006 about the interplay between GABA and 5HT neurons at brainstem level [72]) or following abnormal cortical modulation [53, 54].…”
Section: Relationship Between Cortical Inhibition and Habituation Andmentioning
confidence: 71%
See 2 more Smart Citations
“…In their recent review the authors [8] indeed consider that the reduced HFO, evidenced in somatosensory potential (reflecting a reduced thalamo-cortical activation), could underlie the basal hypo-activity of the sensory cortices. In our opinion the reduced efficiency of inhibitory circuits could represent a valid background to impaired habituation, in migraine as a consistent bulk of evidence supports the reduced activity of inhibitory circuits in migraine [13, 14, 29, 30, 38, 39, 42, 43, 46, 4850]. This could apply not only for cortical but also for sub-cortical structures (see lack of habituation of BR) where it could occur through local GABA dysfunction (see Harsing 2006 about the interplay between GABA and 5HT neurons at brainstem level [72]) or following abnormal cortical modulation [53, 54].…”
Section: Relationship Between Cortical Inhibition and Habituation Andmentioning
confidence: 71%
“…This is because the inhibitory effects of lf-rTMS depend on the integrity of cortical inhibition and evidence in favour of reduced inhibition of visual cortex had been previously reported in TMS papers where the effects of GABA-ergic drugs were evaluated [42] and also in the majority of psychophysical studies [43] with the exception of the data by Shepherd et al 2001, 2006 [44, 45]. Moreover, we also obtained more direct evidence of reduced efficiency of intracortical inhibitory circuits in a further study on motor cortex.…”
Section: Studies Of Cortical Modulation and Evidence Of Reduced Efficmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hyperexcitability of cortical neurons has been implicated in migraine etiology (Welch et al, ). For instance, several studies have demonstrated that the threshold for phosphene generation induced by transcranial magnetic stimulation in occipital cortex was significantly lower in migraine patients during the interictal phase of migraine attack than it is in normal controls (Aurora et al, ; Battelli et al, ; Mulleners et al, ). Moreover, studies of evoked potential have also shown that the cortical responses to repetitive sensory stimulations may be enhanced during the interictal phase of migraine attack in migraine patients (Schoenen et al, ; Ambrosini and Schoenen, ; Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism that has been implicated in migraine is the increased sensitivity of the nervous system of patient who experiences these headaches. Lowering of cortical excitability has also been proposed as one potential mechanism of action of sodium valproate in migraine prophylaxis (39).…”
Section: Introductionmentioning
confidence: 99%